The Shifting Narrative of Character Education in Catholic Schools (2010–2025): A Systematic Literature Review Based on the Lickona Framework - Ambrosius Tode Peya Nia Do; Sugiarto Sugiarto; Desi Rahmawati; Syafa’at Ariful Huda (FKIP - Universitas Riau, 2026)
This literature-based study describes shifts in character education narratives in Catholic schools from 2010 to 2025 using Lickona’s moral framework of knowing–feeling–action. Within conditions of technological disruption and growing social complexity, Catholic schools are portrayed as institutions facing challenges in sustaining moral and spiritual formation while responding to contemporary demands. The review applies a Systematic Literature Review (SLR) design following PRISMA 2020 guidelines, encompassing identification, screening, eligibility, and inclusion stages. A total of 43 articles indexed in Scopus and Web of Science are examined through descriptive and qualitative thematic analysis, with study quality evaluated using the Critical Appraisal Skills Programme (CASP). The synthesis indicates a discernible paradigm shift from a mainly cognitive orientation toward moral knowing (2010–2014) to increased attention to moral feeling and moral action (2015–2025). Values such as service, empathy, integrity, solidarity, and love appear as dominant themes. This shift reflects the reorientation of Catholic education from a dogmatic stance toward a reflective and transformative social practice, with important implications for curriculum development and character formation in pluralistic and secular contexts.